2020
DOI: 10.1021/acscatal.0c02115
|View full text |Cite
|
Sign up to set email alerts
|

Nickel-Catalyzed Dicarbofunctionalization of Alkenes

Abstract: 1,2-Dicarbofunctionalization of alkenes has emerged as an efficient synthetic strategy for preparing substituted molecules by coupling readily available alkenes with electrophiles and/or nucleophiles. Nickel complexes serve as effective catalysts owing to their tendency to undergo facile oxidative addition and slow β-hydride elimination, and their capability to access both two-electron and radical pathways. Two-component alkene functionalization reactions have achieved high chemo-, regio-, and stereoselectivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
93
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 355 publications
(95 citation statements)
references
References 138 publications
1
93
0
1
Order By: Relevance
“…19 Two-component reductive dicarbofuctionalizaton of alkenes via radical cyclization is also possible with Ni catalysis. 20 In this line, we have also shown that vitamin B 12 catalysis enables dicarbofunctionalization of electron-deficient alkenes. 17 The cyclization proposed herein followed by the Giese addition would be the first example of dicarbofuntionalization of non-activated alkenes catalyzed by vitamin B 12 .…”
Section: Paper Synthesismentioning
confidence: 81%
“…19 Two-component reductive dicarbofuctionalizaton of alkenes via radical cyclization is also possible with Ni catalysis. 20 In this line, we have also shown that vitamin B 12 catalysis enables dicarbofunctionalization of electron-deficient alkenes. 17 The cyclization proposed herein followed by the Giese addition would be the first example of dicarbofuntionalization of non-activated alkenes catalyzed by vitamin B 12 .…”
Section: Paper Synthesismentioning
confidence: 81%
“…Early work focused on difunctionalizing 1,1‐disubstituted terminal [7] and bicyclic [8] alkenes to avoid β‐H elimination. Recently, a broad class of substrates were functionalized using a coordination approach [1a–f] in which alkylmetal intermediates were stabilized as transient metallacycles [9] . However, this strategy requires installation and removal of strong coordinating groups like imines, [10] pyridines, [11] 2‐aminopyrimidines, [12] and 8‐aminoquinolines [13] for stabilizing metallacycles [14] .…”
Section: Methodsmentioning
confidence: 99%
“…Nickel-catalyzed alkene 1,2-difunctionalization is considered as useful method for preparing complex molecules in a single-step reaction [137][138][139]. In this aspect, the groups by Kong [140] and Molander [141] independently demonstrated photoredox/nickelcatalyzed approaches to olefin difunctionalizations involving C(sp 3 )-H activation.…”
Section: Olefin Difunctionalizationmentioning
confidence: 99%